2021
DOI: 10.3390/ijerph18052690
|View full text |Cite
|
Sign up to set email alerts
|

Drunkorexia and Emotion Regulation and Emotion Regulation Difficulties: The Mediating Effect of Disordered Eating Attitudes

Abstract: Drunorexia refers to food calorie intake restriction to prevent weight gain and the desire to enhance the more extensive intoxicating effects of alcohol. The present study aimed to investigate the association of drunkorexia with emotion regulation as well as emotion regulation difficulties across the Lebanese population, and assess disordered eating attitudes as a potential mediator of these relationships. The cross-sectional study enrolled participants (n = 258) from all Lebanese districts. The study was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 60 publications
(89 reference statements)
3
14
0
Order By: Relevance
“…Specifically, a previous study conducted in Lebanon concluded that around 28% of the adolescents are at risk of alcohol use disorder, and higher alcohol use disorder was significantly associated with higher cigarette and waterpipe smoking and bullying [27]. Furthermore, higher disordered eating attitudes and higher difficulties in emotion regulation are significantly associated with more drunkorexia motives among Lebanese adults [14]. Since Lebanese government does not have the inaction towards alcohol, in addition to the lack of existing policies regarding the illegal sale or advertisement of alcohol to minors, low excise taxes on alcohol [28], thus it is extremely vital to evaluate all factors associated with alcohol use disorder and drunkorexia among Lebanese population.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Specifically, a previous study conducted in Lebanon concluded that around 28% of the adolescents are at risk of alcohol use disorder, and higher alcohol use disorder was significantly associated with higher cigarette and waterpipe smoking and bullying [27]. Furthermore, higher disordered eating attitudes and higher difficulties in emotion regulation are significantly associated with more drunkorexia motives among Lebanese adults [14]. Since Lebanese government does not have the inaction towards alcohol, in addition to the lack of existing policies regarding the illegal sale or advertisement of alcohol to minors, low excise taxes on alcohol [28], thus it is extremely vital to evaluate all factors associated with alcohol use disorder and drunkorexia among Lebanese population.…”
Section: Introductionmentioning
confidence: 95%
“…All the invited participants were above 18 years of age. The same methodology is described elsewhere [14].…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the role of disordered eating attitudes in the relationship between drunkorexia and emotion regulation, as well as emotion regulation difficulties, has been investigated [ 60 ]. Gender differences in adolescents have also been highlighted [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study claims no difference between pre, peri, and postmenopausal women concerning disordered eating and body shape concerns [ 14 ]. Studies about eating disorders in Lebanon were conducted among the general adult population [ 21 27 ] and adolescents [ 28 30 ], but not on middle-aged women in their menopause phase. The results of international studies are controversial about disordered eating in general and are lacking about orthorexia nervosa in particular.…”
Section: Introductionmentioning
confidence: 99%